Connectome Reorganization Associated With Surgical Outcome in Temporal Lobe Epilepsy. Issue 40 (October 2015) - Ji, Gong-Jun; Zhang, Zhiqiang; Xu, Qiang; Wei, Wei; Wang, Jue; Wang, Zhengge; Yang, Fang; Sun, Kangjian; Jiao, Qing; Liao, Wei; Lu, Guangming
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To identify the distinct pattern of anatomical network reorganization in surgically refractory mesial temporal lobe epilepsy (MTLE) patients using a longitudinal design. We collected longitudinal diffusion-weighted images of 19 MTLE patients before and after anterior temporal lobectomy. Patients were classified as seizure-free (SF) or nonseizure-free (NSF) at least 1 year after surgery. We constructed whole-brain anatomical networks derived from white matter tractography and evaluated network connectivity measures by graph theoretical analysis. The reorganization trajectories of network measures in SF and NSF patients were investigated by two-way mixed analysis of variance, with factors "group" (SF vs NSF) and "treatment" (presurgery vs postsurgery). Widespread brain structures showed opposite reorganization trajectories in FS and NSF groups (interaction effect). Most of them showed group difference before surgery and then converge after surgery, suggesting that surgery remodeled these structures into a similar status. Conversly, contralateral amygdala-planum-temporale and thalamic-parietal tracts showed higher connectivity strength in NSF than in SF patients after surgery, indicating maladaptive neuroplastic responses to surgery in NSF patients. Our findings suggest that surgical outcomes are associated not only with the preoperative pattern of anatomical connectivity, but also with connectome reconfiguration following surgery. The reorganization of contralateral temporal lobe and corticothalamic tracts may be particularly important for seizure control in MTLE.